Setting the Trade Policy Agenda : What Roles for Economists? - Anderson, Kym (World Bank, Washington, DC, 2012)
Economists have influenced the trade policy agenda for establishing multilateral trade rules, disciplines, and procedures, and for negotiating most-favored nation and preferential reductions in trade barriers and subsidies, in addition to affecting the agenda for unilateral policy reform. These roles are considered in turn, before focusing on the economists' contribution through quantifying the extent and effects of existing trade distortions and alternative reform initiatives. Many trade distortions remain, however, so the author looks at where trade economists' efforts in agenda-setting need to be focused in the years ahead.